Evoluție prin instruire: Evaluarea impactului formării profesionale continue a personalului Bibliotecii Municipale „B.P. Hasdeu” - Țurcan, Nelly (BIBLIOPOLIS, 2024)
The study emphasizes the importance of continuous professional development in enhancing the efficiency and competence of the staff at the “B.P. Hasdeu” Municipal Library. On-going evaluation of training activities is necessary to uphold service quality and to guarantee alignment with user needs and technological advancements. The ADDIE model (Analyse, Design, Develop, Implement, and Evaluate) is used by the “B.P. Hasdeu” Municipal Library to structure and enhance training programs. In order to evaluate the activity of the Continuous Training Centre for Librarians at the “B.P. Hasdeu” Municipal Library (Campus of Competences), a survey was conducted among 57 librarians who participated in training activities in 2023. The results of the survey show that continuous development contributes to improving professional competencies, creating a motivating work environment, and effectively adapting to changes. The Campus of Competences at the “B.P. Hasdeu” Municipal Library is appreciated for the efficient organisation of professional training and the competence of the trainers, and is considered an important factor for the professional success of the employees. The survey also suggests the need to diversify the topics covered in the training programmes to better meet the specific needs of librarians. Continuous evaluation of the training’s impact allows for the identification and correction of gaps, reinforcement of strengths, and quick adaptation to new requirements. This process showcases the “B.P. Hasdeu” Municipal Library’s dedication to excellence and innovation, thereby upholding a high standard of professionalism and relevance to the local community.